Geología de los cuadrángulos de Bagua Grande, Jumbilla, Lonya Grande, Chachapoyas, Rioja, Leimebamba y Bolivar. Hojas: 12-g, 12-h, 13-g, 13-h, 13-i, 14-h y 15-h – [Boletín A 56] - Sánchez Fernández, Agapito Wilfredo (1995)
287 p.